Structural vulnerability of two traditional Portuguese timber structural systems - Murta, António (2012)
In general, the traditional Portuguese buildings show an undesirable deterioration level and, consequently, urgent rehabilitation processes are required. These buildings need maintenance and preservation because they are a valuable Portuguese heritage. Knowing and understanding these buildings is the first step for adequate rehabilitation processes. Usually, these buildings show the same pattern of pathologies and failure sequence. This research work is focused on the study of the roof timber structural systems of these buildings and intends to highlight these aspects. An expedite methodology of structural vulnerability assessment of the traditional Portuguese timber roof structures based on the structural vulnerability theory is presented. Real cases of traditional Portuguese timber roof structures are used. It was concluded that the trussed timber roof system seems less robust than the beamed system. (c) 2010 Elsevier Ltd. All rights reserved.